Implementation of The Cabotage Principle on Good Governance as The World Maritime Axis - Sudirman (Hang Tuah Law Journal, 2019)
The research problem of this study is implementation of the Cabotage Principle in Indonesia in accordance with Law Number 17 of 2008 concerning Shipping has implications for Indonesia's positive law. The implementation of the Cabotage Principle is an integral part of the Archipelago Insight and is the basis for realizing Good Governance as the World Maritime Axis and will have positive implications if the Cabotage Principle is based on the Good Governance principles as the World Maritime Axis. The ideal implementation of the Cabotage Principle for the interests of Indonesia as the World Maritime Axis is determined by the synergy of three element of the legal system, namely the legal structure (structure of law), legal substance (substance of the law) and legal culture (legal culture). So that the Cabotage Principle as a Grundnorm can function properly, namely as social control, dispute settlement, and a tool of social engineering.